Bible Beliefs, Conservative Religious Identity, and Same‐Sex Marriage Support: Examining Main and Moderating Effects. Issue 4 (18th November 2015) - Perry, Samuel L.
Abstract : Research finds that Americans who espouse theologically conservative beliefs about the Bible generally oppose same‐sex marriage. Studies exploring this link, however, have been limited in that their operationalization of fundamentalist belief has been problematically conceptualized and they have potentially confounded the effect of conservative religious identity. The current study asks: (1) How do distinct beliefs about the nature and authority of the Bible influence same‐sex marriage support? (2) Do these beliefs influence same‐sex marriage support independently of conservative religious identity? (3) To what extent do Bible beliefs and conservative religious identity moderate one another's effects? And (4) to what extent are these factors moderated by religious tradition and frequency of Bible reading? Analyses of 2006 Portraits of American Life Study data reveal that while identifying as religiously conservative is the strongest predictor of opposition to same‐sex marriage, believing in inerrancy and creationism remain strong predictors in full models. I also find moderating effects between belief in creationism, inerrancy, inspiration; religious‐conservative identity; and religious tradition. Findings clarify how theological beliefs and religious identity shape support for same‐sex marriage across religious traditions.